Can referees assess head contact penalties correctly in canadian youth ice hockey? A video analysis study - Williamson, R. A.; Kolstad, A. T.; Eliason, P. H.; Hagel, B. E.; Emery, C. A. (Clinical Journal of Sport Medicine, 2023)
Objective: To help address the high concussion burden in Canadian youth ice hockey, our primary objective was to examine the concurrent validity of youth ice hockey referees' ability to assess head contacts (HCs) and associated penalties using video analysis methods after implementation of the "zero tolerance for HC" policy by Hockey Canada.